Effects of COVID-19: relations of sport and disability on the training load and expectation of athletes on road to Tokyo Paralympic Games - Trigo, E. L.; Willig, R.; Melo, G. L.; Ahmadi, S.; Costa, S. G.; Almeida, R. M.; Ferraiera, M.; Araujo, V. L.; Castilho, R.; Winckler, C. (Medicina dello Sport, 2022)
BACKGROUND The prevention protocols of COVID-19 impact several restrictions in the sports world, the influence of this scenario in the athletes with impairment increased associated a multifactorial condition like environment, etiology, or psychological perception. The aim of this study was to identify the influences of impairments and sports on characteristics of load training during the COVID-19 Pandemic, life satisfaction and the expectation about the influence of pandemic on the performance in the Tokyo 2020 Paralympic Games.